(untitled) (Journal of Economic Research & Business Administration, 2015)
In this article a methodology for determining the innovative development of the industry of Kazakhstan was proposed. Management through the allocation of mesoobjects was proposed.We identified mesolevel, according its technological level and sub-mesolevel – subtypes of economical activity. The analysis of the structure of the manufacturing industry was presented. We calculated and presented the share of medium-low-tech, low-tech, medium-high and high-tech types of industries in the total volume of innovative products. The concentration of the innovative activity was identified. We concluded that the concentration of innovation is higher in medium-high-tech and high-tech kinds of industries that is necessary to develop. In a behavioral aspect also it is need to stimulate these types. On the basis of this methodology, we can identify problem points, as well as stimulus, anti-stimulus, input into the innovation process and we can manage the innovation process, namely developing the types of production, which were described above